Chiral NHC/Cu(I)-Catalyzed Asymmetric Hydroboration of Aldimines: Enantioselective Synthesis of α-Amido Boronic Esters - Zhang, Shu-Sheng; Zhao, Yi-Shuang; Tian, Ping; Lin, Guo-Qiang (Synlett, 2013)
Non-C2-symmetric (N-alkyl, N-aryl)-hybrid chiral NHC/Cu(I) complex catalyzed asymmetric hydroboration of N-benzoyl aldimines has been developed. The reaction proceeded smoothly at room temperature, giving α-amido boronic esters in excellent yields (up to 94%) and good enantioselectivities (up to 86% ee).
Keywords: chiral NHCs; copper; asymmetric hydroboration; aldimines; α-amido boronic esters